DaMatta revisited: Houses and the spatiality of respect relations in Northeast Brazil. (1st September 2016) - Shapiro, Matan
Abstract: Roberto DaMatta famously argues that in the Brazilian cultural universe stable moral codes buttress familial hierarchy in the house, while situational negotiations underscore egalitarian utopias in the street. In this article, I revise this analytic construct, which a priori assumes that the person of the house and the "individual" of the street are mutually exclusive social categories. Rather than polarize house and street as distinct cultural domains diametrically opposed to one another, I demonstrate ethnographically that houses in the Brazilian state of Maranhão are conceptually continuous with the street to varying degrees. I argue that moral indebtedness in both these domains locally manifests through the emotional economies of respect ( respeito ), by which persons/individuals introduce measures of emotional proximity or distance into various types of material exchange relations. Both men and women ultimately channel these types of relations into the space of their family houses, which thus become hubs for the circulation of core social values.